2006
DOI: 10.1097/01.ico.0000220775.93852.02
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Lidocaine or Bupivacaine on Corneal Endothelial Cells in a Rabbit Model

Abstract: One-minute exposure to lidocaine 1% E or 2% E appears to be safe for cultured rabbit CECs, although longer exposures could cause time-dependent cytotoxicity, which should be considered in planning cataract or other ocular surgery. Because bupivacaine 0.5% and 0.5% spinal heavy cause cytotoxic effects within the first minute of contact with CECs, they should be used with great caution, if at all, in the anterior chamber of human eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 32 publications
1
45
0
1
Order By: Relevance
“…The characteristic lesion begins in the periphery of the cornea and spreads circumferentially (6). The leading edges of the ulcer are undermined, infiltrated and de-epithelialized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic lesion begins in the periphery of the cornea and spreads circumferentially (6). The leading edges of the ulcer are undermined, infiltrated and de-epithelialized.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying toxic keratopathy may include damage of the corneal epithelial barrier and disruption of re-epithelialization (6). A healthy epithelial surface protects the cornea from potential infection and the invasion of various microbial pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Although topical anaesthesia is very popular in some countries, caution is required. Chang et al, 11 for example, have demonstrated in a rabbit model that local anaesthetic drops can cause dose and time-dependent cytotoxicity, usually within the first minute of contact with corneal endothelium. Guzey et al 12 have demonstrated the risks of corneal endothelium damage following the application of topical anaesthesia in patients.…”
Section: Sub-tenon's Blockmentioning
confidence: 99%
“…It can result in corneal thickening, opacification and significant corneal endothelial cell loss when applied intracamerally [12]. In addition, administration of lidocaine has been shown to cause an increase in apoptotic cells in corneal endothelium in rabbit models [13]. However, the side effects of lidocaine on HCE cells and their mechanism remain unknown.…”
mentioning
confidence: 99%